Reproductive isolation between oviparous and viviparous lineages of the Eurasian common lizard Zootoca vivipara in a contact zone. (10th February 2015) - Cornetti, Luca; Belluardo, Francesco; Ghielmi, Samuele; Giovine, Giovanni; Ficetola, Gentile F.; Bertorelle, Giorgio; Vernesi, Cristiano; Hauffe, Heidi C.
Abstract: Contact zones between two evolutionary lineages are often useful for understanding the process of speciation because the observed genetic pattern reflects the history of differentiation. The Eurasian lacertid lizard Zootoca vivipara is a potentially interesting model for studying the role of reproductive mode in the speciation of squamate reptiles because it has both oviparous ( Zootoca vivipara carniolica ) and viviparous ( Zootoca vivipara vivipara ) populations that have recently been shown to be genetically distinct. We studied a newly-discovered syntopic area of these two Zootoca subspecies in the central Italian Alps using genetic markers to investigate the level of introgression between them. Patterns of genetic differentiation in a fragment of the mitochondrial DNA cytb gene and a set of nuclear microsatellites show that the speciation process is complete in this area, with no evidence of recent introgression. Phylogenetic and genotypic divergence suggests that the two subspecies have experienced long independent evolutionary histories, during which genetic and phenotypic differences evolved. The possible roles of biogeography, reproductive mode, and cytogenetic differentiation in this speciation process are discussed.